2018
DOI: 10.1002/cam4.1394
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical prognostic model for risk stratification in patients with early breast cancer according to 18F‐fludeoxyglucose uptake and clinicopathological parameters

Abstract: This study was to investigate a hierarchical prognostic model using clinicopathological factors and 18F‐fludeoxyglucose (FDG) uptake on positron emission tomography/computed tomography (PET/CT) for recurrence‐free survival (RFS) in patients with early breast cancer who underwent surgery without neoadjuvant chemotherapy. A total of 524 patients with early breast cancer were included. The Cox proportional hazards model was used with clinicopathological variables and maximum standardized uptake value (SUVmax) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Interestingly, despite its lower prevalence, the luminal subtype showed similar recurrence to other subtypes, which is different from early breast cancer in which the luminal subtype showed less recurrence compared with the HER2-enriched and TN subtypes. 26 In this study, we found recurrence in 13/28 (46%) with luminal, 3/9 (33%) with HER2-enriched, and 7/18 (39%) with TN subtypes.…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, despite its lower prevalence, the luminal subtype showed similar recurrence to other subtypes, which is different from early breast cancer in which the luminal subtype showed less recurrence compared with the HER2-enriched and TN subtypes. 26 In this study, we found recurrence in 13/28 (46%) with luminal, 3/9 (33%) with HER2-enriched, and 7/18 (39%) with TN subtypes.…”
Section: Discussionsupporting
confidence: 54%
“…After excluding duplications and meeting summaries, 69 articles that did not meet the inclusion criteria were removed. Finally, 20 studies including 3,115 patients that met the conditions of the study and published from 2013 to 2019 were included in this meta-analysis[6, 7, 9, 1127] (Fig 1). All 20 studies reported the prognostic values of SUVmax, MTV or TLG for BC survival.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies developed a prognostic model using [ 18 F]FDG PET/CT parameters for hepatocellular carcinoma and breast cancer 23 , 24 ; however, a prognostic model using a combination of T_SUVmax and N_SUVmax has not been reported for GC. Accordingly, we developed and internally validated a new staging system that comprises a combination of the metabolic score and the conventional TNM stage, which are independent prognostic factors for DSS in GC patients.…”
Section: Discussionmentioning
confidence: 99%